Synthesis and Spectroscopic Studies of Substituted Three Different vic-Dioximes with New Binuclear Zn(II) Complexes - Duman, Sibel; Sekerci, Memet (Asian Journal of Chemistry, 2010)
The synthesis, spectroscopic properties of Zn(II) metal complexes with three novel substituted amino vic-dioxime ligands, N,N'-[2,2'-{ethane-1,2-di-yl-bis(oxy)bis(2,1-phenylene)}bis(N'- hydroxy)-2-(hydroxyimino)acetamidamide] (L1H4), N,N'-[3,3'-{ethane-1,2-di-yl-bis(oxy)bis(3,1- phenylene)}bis(N'-hydroxy)-2-(hydroxyimino) acetamidamide] (L2H4) and N,N'-[4,4'-{ethane- 1,2-di-yl-bis(oxy)bis(4,1-phenylene)}bis(N'-hydroxy)-2-(hydroxyimino) acetamidamide] (L3H4), prepared 1,2-bis(o-aminophenoxy)ethane, 1,2-bis(m-aminophenoxy)ethane and 1,2-bis(p-aminophenoxy) ethane with antichloroglyoxime are reported. The structure of these amino vicdioximes have been as the antiform according to 1H NMR and FT-IR data. The metal to ligand ratio of Zn(II) complexes are found to be 2:2. The Zn(II) complexes of these ligands are proposed to be tetrahedral or octahedral. The structures of ligands and their complexes are proposed from elemental analyses, FT-IR, UV vis, 1H NMR, magnetic susceptibility measurements and TGA-DTA analysis.